2021
DOI: 10.1016/j.dyepig.2020.108908
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical properties of dyads composed of porphyrin/ruthenium catalyst grafted on metal oxide semiconductors

Abstract: In the current work, we present the use of two free-base and two zinc-metallated porphyrinruthenium(II) polypyridine dyads, along with two reference porphyrin derivatives, as sensitizers in both n-and p-type DSSCs and DSPECs. Two of the dyads contain the well-known Ru(bpy)3 unit (HOOC-DMP-Ru(bpy)3 and HOOC-(Zn)DMP-Ru(bpy)3), while in the other two terpyridine-Ru(Cl)-bypiridine was used (HOOC-DMP-tpy-Ru and HOOC-(Zn)DMP-tpy-Ru). In all systems, the amide-bonding motif was utilized for the connection of the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Subsequently, the carboxylic acid anchoring group was converted into hydroxamic acid by using hydroxylamine hydrochloride, affording the hyd-ZnP-TEMPO dyad. The synthetic procedure of the reference derivative HO 2 C-ZnP has been previously reported from our group, 34 while the reference compound hyd-ZnP was prepared following similar reactions (Scheme S2). The successful synthesis of all the final and intermediate compounds was verified via 1 H and 13 C NMR spectroscopies (Figures S26-S34, ESI † ), and MALDI-TOF mass spectrometry.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the carboxylic acid anchoring group was converted into hydroxamic acid by using hydroxylamine hydrochloride, affording the hyd-ZnP-TEMPO dyad. The synthetic procedure of the reference derivative HO 2 C-ZnP has been previously reported from our group, 34 while the reference compound hyd-ZnP was prepared following similar reactions (Scheme S2). The successful synthesis of all the final and intermediate compounds was verified via 1 H and 13 C NMR spectroscopies (Figures S26-S34, ESI † ), and MALDI-TOF mass spectrometry.…”
Section: Synthesismentioning
confidence: 99%
“…On the other hand, the performances of DSPECs are usually modest, most certainly because the dye must feed the catalyst with several redox equivalents before catalysis occurs. This requirement is particularly demanding in the context of a photosensitized electrode because it implies that (i) the dye photoexcitation frequency is high, so that the same dye absorbs photons at close intervals in order to funnel several charges to the catalyst before charge recombination takes place, which is a difficult task with the low photon flux of sunlight or (ii) the lateral charge diffusion inside the monolayer of the chemisorbed molecules is quite efficient, at least faster than charge recombination, so that several different oxidized dyes could feed the catalyst with oxidation equivalents. As a result, choosing an oxidation reaction which involves only two oxidizing equivalents, instead of four, could be a nice opportunity to alleviate the challenging multiple charge accumulation step in DSPECs. On this field, the seminal work of Meyer and co-workers was followed by a few other studies, ,, but alcohol oxidation in DSPECs still remains an unexplored scientific topic today, particularly if one compares it with water oxidation. , All the previously reported studies of alcohol oxidation with DSPECs that we are aware of rely on a ruthenium polypyridine complex as the catalyst ,,, and very often with a ruthenium tris-bipyridine-based TiO 2 sensitizer, although a few publications describe systems with an organic sensitizer. ,,, Very recently, an interesting study has reported a DSPEC type photoanode made of a TiO 2 film sensitized by a ruthenium tris-bipyridine complex that depolymerizes lignin with the N -hydroxyphthalimide catalyst solubilized into an acetonitrile-based electrolyte . A catalytic photocurrent density of about 130 μA/cm 2 was measured upon light irradiation (200 mW/cm 2 ) with an applied potential of 0.75 V versus a saturated calomel electrode (SCE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalytic process mainly involves the photosensitive moiety absorbing photons, generating electron−hole pairs under illumination, and undergoing charge separation and transfer under the action of the built-in electric field, thereby effectively driving water splitting. At present, there are two main factors limiting the efficiency of solar water splitting: 4 (1) The electron−hole pairs generated from the photocatalyst by absorbing photons under light irradiation are prone to rapid recombination. (2) Hydrogen production from water splitting involves a complex kinetic process of fourelectron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the free-base H 2 P-Ru dyad was synthesized via a complexation reaction between the previous two intermediates, namely TPP-bpy and Ru(bpy(COOMe) 2 ) 2 following known experimental procedures. 32 The final step was a metalation reaction to insert Ni( ii ) inside the porphyrin core affording the NiP-Ru dyad. The hydrolyzed dyad derivative NiP-Ru-COOH , bearing four carboxylic anchoring groups was obtained via basic hydrolysis.…”
mentioning
confidence: 99%